1996
DOI: 10.1021/jo961019g
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Cathodically-Promoted and Base-Catalyzed Michael Addition Reactions of Levoglucosenone

Abstract: Regioselective Michael addition of nitro and heterocyclic compounds to levoglucosenone, 1, is effectively catalyzed by amines and also by cathodic electrolysis. In comparison to the base-catalyzed reaction, it was found that under electrochemical conditions the reaction proceeds under milder conditions and with higher yields. Cathodically-initiated Michael addition of thiols to levoglucosenone using small currents produces the previously unknown threo addition product in several instances. The normal erythro i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…It is unclear from theses tudies if Cyrenei sa na ctive substrate for the enzymes or if there are other problemsf or biocatalytic processes( see below). [59] As expected, Cyrene was also not ag ood solventf or the preparation of 2,4,5-trisubstituted-2-imidazolines 47 from the condensation reactiono fa ldehydes,s uch as 4-(trifluoromethyl)benzaldehyde (46), and ammonium carbonate (Scheme 12). [60] Instead of the desired product, ac omplex reaction mixture was obtained, which was presumably the result of the reactionoft he solvent with the reagents.…”
Section: Use Of Cyrene As Abio-available Solventmentioning
confidence: 66%
See 2 more Smart Citations
“…It is unclear from theses tudies if Cyrenei sa na ctive substrate for the enzymes or if there are other problemsf or biocatalytic processes( see below). [59] As expected, Cyrene was also not ag ood solventf or the preparation of 2,4,5-trisubstituted-2-imidazolines 47 from the condensation reactiono fa ldehydes,s uch as 4-(trifluoromethyl)benzaldehyde (46), and ammonium carbonate (Scheme 12). [60] Instead of the desired product, ac omplex reaction mixture was obtained, which was presumably the result of the reactionoft he solvent with the reagents.…”
Section: Use Of Cyrene As Abio-available Solventmentioning
confidence: 66%
“…471 and 487) with aL D 50 > 2000 mg kg À1 (OECD No. [44] In related6 ,8-dioxabicyclo[3.2.1]octanone ring systemsi nw hich there is as ubstituent at the b-position, such as alcohol 24 [45] or pyrazole 25, [46] the ketal form can be isolated and characterized. [42] Althoughith as been given ah azard warning for being an eyei rritant (E319), Cyrene has received ECHA level 7c ertification.…”
Section: Use Of Cyrene As Abio-available Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11] Actually, depending on the electrolysis procedure, the authors showed two different processes targeted at 2-nitro alcohols or 1,3-dinitro compounds. [12] We have now found that, under the conditions reported above, the direct electrolysis of pure nitromethane, under an inert atmosphere, could be conveniently used for a selective synthesis of the 2-nitro alcohols 6 by addition of an aldehyde 5 to the cathode compartment at the end of the electrolysis (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…A study into the hydration of Cyrene (1) was undertaken in order to better understand why it could be separated from the product amide via the addition of water. Whilst the hydrate of Cyrene 7 31 as well as related 6,8-dioxabicyclo[3.2.1]octanone ring systems in which there is a substituent at the -position are reported, 32,33 at the start of our study there is was no NMR data available for the hydrate or information on the effect of water concentration on the equilibrium. Very recently, De bryun et al reported on the hydration of Cyrene (1) and the ability of the solutions to solvate simple organic compounds.…”
Section: Investigation Into the Hydration Of Cyrene (1)mentioning
confidence: 95%